Gas Chromatographic (GC-GC/MS) Analysis of Essential Oil of Phlomis armeniaca Willd. from Mediterranean Region in Turkey - Yasar, S.; Fakir, H.; Erbas, S. (Asian Journal of Chemistry, 2010)
The chemical composition of the essential oil obtained by hydro-distillation from aerial parts of the endemic Phlomis armeniaca Willd. (Lamiaceae) collected from mediterranean region, C3 Beskonak (Antalya), Koprulu Canyon National Park in Turkey has been studied. Twelve components were identified composing 91.78 % of the essential oil of P. armeniaca. P. armeniaca essential oil contained germacrene-D (35.68 %), β-caryophyllene (18.08 %), caryophyllene oxide (13.35 %), (E)-β-farnesene (7.24 %) and hexahydrofarnesyl acetone (6.99 %) as main components. Germacrene-D was the dominant and distinctive compound of Phlomis armeniaca Willd.